Dampak Kesehatan Dan Keselamatan Kerja, Beban Kerja, Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan - Vani Kenanga Nan Wangi; Eloh Bahiroh; Ali Imron (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
This study aims to analyze the effect of Occupational Health and Safety, workload, and physical work environment for employee performance PT. Arwana Citra Mulia Tbk. In this research, there are four variables named Occupational Health and Safety (X1), Workload (X2), physical work environment (X3), and employee performance (Y). This study involved 50 samples of production division employees at PT. Arwana Citra Mulia Tbk. This study uses data collection methods in the form of interviews, observations, questionnaires. In this research, data analysis methods that were used are descriptive analysis, data quality test, classic assumption test, t test using SPSS calculations. The results of this study show that: (1) Occupational Health and Safety do not have positive and significant impact on employee performance (2) Workload does not have negative and significant impact on employee performance (3) physical work environment does have positive and significant impact on employee performance.